2001
DOI: 10.1034/j.1600-0447.2001.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicides are seldom prescribed antidepressants: findings from a prospective prescription database in Jämtland county, Sweden, 1985–95

Abstract: There is a frequent use of psychotropics and psychiatric care among suicides; however, few used antidepressants and complied. Many suicides are still misdiagnosed and are not adequately treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 23 publications
5
50
1
3
Order By: Relevance
“…Suicidal behavior correlates with inadequate prescription of antidepressants, 32 and from 1978 to 1997, the proportion of the outpatient US population with depression receiving at least 1 antidepressant prescription increased from 37.3% to 74.5%. 8,10,43 Mood disorders accounted for 45% of all antidepressant prescriptions in 1997 and 59% in 2000, 31 so both the proportion and therefore the impact of more prescriptions on mood disorders are likely to have been sustained over this limited period for which we have data.…”
Section: Commentmentioning
confidence: 99%
“…Suicidal behavior correlates with inadequate prescription of antidepressants, 32 and from 1978 to 1997, the proportion of the outpatient US population with depression receiving at least 1 antidepressant prescription increased from 37.3% to 74.5%. 8,10,43 Mood disorders accounted for 45% of all antidepressant prescriptions in 1997 and 59% in 2000, 31 so both the proportion and therefore the impact of more prescriptions on mood disorders are likely to have been sustained over this limited period for which we have data.…”
Section: Commentmentioning
confidence: 99%
“…Furthermore, the perception of functional impairment, is often more critical in suicidality than the objective disability produced by disease (11,12), again testifying to the importance of depressive cognitions. ThatÕs why it is tragic that most individuals who commit suicide in the community had rarely received the benefit of adequate pharmacologic, psychotherapeutic or electroconvulsive treatment for depression (13)(14)(15)(16).…”
Section: ôDepressionõ As the Final Common Pathway In Suicidementioning
confidence: 99%
“…Swedish studies in 1970-1984 and 1985-1995 found that only 15% and 12% of individuals who committed suicide in the Swedish county of Jämtland during those periods had filled prescriptions of antidepressants during their last three months before suicide (Henriksson, Boethius & Isacsson, 2001;Isacsson, Boëthius & Bergman, 1992). The San Diego study (1981)(1982)(1983) found that only 23% of suicides diagnosed post-mortem with major, bipolar, or atypical depression had been prescribed antidepressants within 90 days of death (Isacsson, Bergman & Rich, 1994a).…”
Section: Under-treatment With Antidepressantsmentioning
confidence: 99%